A 24‐week, randomized, double‐blind, active‐controlled clinical trial comparing bexagliflozin with sitagliptin as an adjunct to metformin for the treatment of type 2 diabetes in adults. Issue 10 (30th June 2019) - Halvorsen, Yuan‐Di; Lock, John P.; Zhou, Wenjiong; Zhu, Fang; Freeman, Mason W.
Abstract: Aim: To compare the relative safety and effectiveness of bexagliflozin and sitagliptin as adjuncts to metformin for the treatment of adults with type 2 diabetes. Methods: Participants (n = 386) were randomized to receive bexagliflozin (20 mg) or sitagliptin (100 mg) in addition to their existing doses of metformin. The primary endpoint was the non‐inferiority of bexagliflozin to sitagliptin for change in HbA1c from baseline to week 24. Changes from baseline to week 24 in fasting plasma glucose (FPG), body mass (in subjects with baseline body mass index ≥25 kg m −2 ) and systolic blood pressure (SBP) were secondary endpoints. Results: The mean change from baseline to week 24 in HbA1c was −0.74 (95% CI −0.86%, −0.62%) in the bexagliflozin arm and −0.82% (95% CI −0.93%, −0.71%) in the sitagliptin arm, establishing non‐inferiority. The changes from baseline FPG, body mass and SBP were −1.82 mmol L −1, −3.35 kg and −4.23 mmHg in the bexagliflozin arm and −1.45 mmol L −1, −0.81 kg and −1.90 mmHg in the sitagliptin arm, respectively. These differences were significant for the first two measures (one‐sided P = 0.0123, P < 0.0001 and P = 0.0276, respectively.) Adverse events were experienced by 47.1% of subjects in the bexagliflozin arm and 56.0% of subjects taking sitagliptin. Serious adverse events affected 3.7% of subjects in the bexagliflozin arm and 2.1% of subjects in the sitagliptin arm. Conclusions: Bexagliflozin was non‐inferior to sitagliptin and provided benefits over sitagliptin in FPG and body mass. Adverse event incidences in the two arms were similar.